KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN PENGUNJUNG DI UPT PERPUSTAKAAN UNIVERSITAS RIAU - Sudana, Robby; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Library is successful if it had been able to meet the needs and expectations of users. But until now Riau University Library Unit is still constrained by the quality of services provided such as:1. The number of collections that are less meet the needs of visitors, as well as the lack of new books published in Library Unit.2. The existing information systems today are still many problems.3. System of preparation of the book is still not organized.4. Less friendly and less of a response employees / officers in providing services.This study aims to determine the quality of service in improving visitor satisfaction in Riau University Library Unit and to investigate the factors that influence the quality of service in improving visitor satisfaction in Riau University Library Unit. Tjiptono theoretical concept in Hardiyansyah (2011: 40) There are six indicators to determine the quality of public services, namely: 1. Timeliness of care services 2. Accuracy 3. Courtesy and friendliness 4. Ease of getting care 5. Convenience in obtaining support services 6. Attribute servicing , This research method used descriptive qualitative method, ie the data obtained will be discussed thoroughly by the reality that occurs in institutions or where research is conducted. Then compared with the concepts and theories that support the discussion of the problems in this study, and then draw conclusions that are generally applicable.From the results of research and discussion conducted on "Quality of care in improving visitor satisfaction in Riau University Library Unit", it can be argued that the UPT service Riau University Library has been implemented but not maximum quality of services provided to library patrons. This is a drawback that can be used as a reference for the Riau University Library Unit in order to improve the quality of its services so as to improve the satisfaction of users of the library.Key words: Services, Visitor Satisfaction.